Ferritin in hypertensive and diabetic women before and after bariatric surgery - Marin, Flavia Andreia [UNESP]; Rasera Junior, Irineu [UNESP]; Souza Leite, Celso Vieira de [UNESP]; Marques de Oliveira, Maria Rita [UNESP] (Aula Medica Ediciones, 2015)
In addition to its important role as marker of iron stores, serum ferritin is a marker of systemic inflammation, and obesity has been associated with chronic inflammation.Objective: To verify, six months after surgery, the effect of bariatric surgery on the serum ferritin of women who were hypertensive, diabetic, or comorbidity free before surgery.Sample and methods: This retrospective study included 200 women aged 20 to 45 years, with a body mass index (BMI) equal to or greater than 35 kg/m(2), submitted to Roux-en-Y gastric bypass (RYGB). Seventy of these women were hypertensive, forty had type 2 diabetes (T2D), and ninety were comorbidity free (CF). They were assessed before and six months after surgery. Anthropometric, laboratory (serum ferritin and hemoglobin), and comorbidity-related data were collected from their medical records.Results: Before surgery, women with comorbidities were older, the hypertensives had higher BMI, and the diabetics had higher serum ferritin levels than the CF women. The study comorbidities had resolved in 68% of the hypertensive women and 86% of the diabetic women six months after RYGB. Also at this time, the serum ferritin of hypertensive women decreased from 110.1 +/- 86.3 to 88.7 +/- 80.5 ng/dL and of diabetic women, from 164.8 +/- 133.4 to 101.2 +/- 97.7 ng/dL (p<0.05); hemoglobin also decreased in hypertensive and CF women (p>0.05).Conclusion: High ferritin in premenopausal obese women was associated with the main obesity-related comorbidities, and these comorbidities determined the reduction of serum ferritin after bariatric surgery.

Además de importante marcador de las reservas de hierro, la ferritina sérica es un marcador de la inflamación sistémica, mientras que la obesidad se ha asociado con la inflamación crónica. Objetivo: Identificar, después de 6 meses, el efecto de la cirugía bariátrica sobre los niveles de ferritina sérica en hipertensos, diabéticos o sin estas comorbilidades preoperatorias mujeres. Pacientes y métodos: Los autores realizaron un estudio retrospectivo de 200 mujeres sometidas a bypass gástrico en Y de Roux (BGYR), con edades comprendidas entre 20 y 45 años, con un índice de masa corporal (IMC) superior a 35 kg/m2, con hipertensión arterial (HA, n = 70), la diabetes mellitus tipo 2 (DM2, n = 40) y sin comorbilidades (SC, n = 90) fueron evaluados antes y 6 meses después de BGYR. Antropométricas, de laboratorio (ferritina sérica y hemoglobina) y la información de comorbilidad se recogió de la historia clínica electrónica. Resultados: Antes de la cirugía, las mujeres con comorbilidades eran mayores, tenían mayores hipertensos IMC, niveles más altos de ferritina diabéticos en relación con el grupo SC. La resolución de las comorbilidades después de 6 meses de DGYR ocurrió en el 68 % de las mujeres con hipertensión y el 86 % de los diabéticos. 6 meses después de la cirugía, se observó una disminución de la ferritina sérica en mujeres con comorbilidades de 110,1 ± 86,3 a 88,7 ± 80,5 ng/dl en el grupo con hipertensión y 164,8 ± 133,4 a 101 2 ± 97,7 ng/dl en DM2 (p < 0,05) y la hemoglobina, excepto en los pacientes diabéticos (p > 0,05). Conclusión: El aumento de la ferritina en mujeres obesas en el periodo de premenopausia se relacionan con las principales comorbilidades de la obesidad, y la presencia de estas comorbilidades fue fundamental en la reducción de la ferritina sérica después de la cirugía bariátrica.
La ferritina en mujeres hipertensas y diabéticas antes y después de la cirugía bariátrica
Keywords: Ferritin; Inflammation; Obesity; Comorbidities; Bariatric surgery; La ferritina; Inflamacion; La obesidad; Comorbilidades; La cirugia bariatrica